Mengungkap Pendidikan Peran dan Identitas Perempuan dalam Al Qur’an Melalui Kajian Kata Nisa’, Niswah dan Imra’ah - Hayy, Nasmah Muti’ah; Maghfiroh, Khoirun Nisail; Rofi'i, Muhammad Arwani (QuranicEdu: Journal of Islamic Education, 2025)
This article aims to explore the education of roles and identities of women in the Qur’an through a linguistic study of the terms Nis?’, Niswah, and Imra’ah. Although these three terms generally refer to the female gender, they carry different nuances and contextual meanings within the Qur’anic text. These distinctions reflect the diverse roles and identities of women both in society and within the framework of Islamic teachings. This study employs a qualitative descriptive method with a library research approach. Data were collected from Qur’anic verses containing the aforementioned terms and were supported by classical and contemporary tafsir (exegesis) and relevant scholarly literature. The analysis focuses on both the literal and contextual meanings of each term and examines their implications in understanding the concept of women in Islam. The findings indicate that Nis?’ refers to adult women in a general and unrestricted sense, Niswah refers to a specific group of women in particular contexts, while Imra’ah denotes an individual woman. Despite the variations in usage and interpretation in society, all three terms bear the same legal (shar‘i) implications in Islam, referring equally to the obligations of a Muslim woman. This study is expected to contribute to the enrichment of Qur’anic scholarship, particularly in the fields of gender and Qur’anic linguistics.